After the Great Recession: Unions’ Views on Transnational Interests and Cooperation - Bengtsson, Mattias; Vulkan, Patrik (Nordic Journal of Working Life Studies, 2018)
The aim is to describe and explain the similarities and differences between European trade unions concerning their views on transnational union interests and cooperation in the wake of the Great Recession. We do this by analyzing 221 responses from a European-wide web/postal survey distributed in 2015–2016 to union officials representing staff in employment sectors such as transport, metal and mining, construction, health care, and banking and finance. We find only limited sectoral differences, despite the varied impact of the Great Recession. The main findings are that unions in crisis-ridden southern European countries express a stronger orientation toward transnational union interests and cooperation. Unions in the northern and western European center express a weaker transnational orientation, in line with a renationalization strategy typically expressed in the form of national competitive corporative arrangements. This shows the importance of different institutional resources for unions across the various European industrial relations regimes.